2016
DOI: 10.1007/s11015-016-0177-y
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Treatment of Rolled Products Used to Make Long High-Strength Bolts

Abstract: The set of structural-mechanical properties of steel 40X has been optimized in preparation for the cold upsetting of long high-strength bolts. The properties were optimized by analyzing different factors that determine the quality of the sized rolled products used for the production of hardware items by cold upsetting. An effi cient method was developed to prepare steel 40X rolled products with diameters of 9.65 and 11.7 mm and a 9.8 strength rating for the production of long high-strength short-head bolts wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 1 publication
0
14
0
1
Order By: Relevance
“…Детали автомобиля изготавливаются по разным технологиям [11 -13]. Однако изучение деструкции материалов при усталости осложняется длительностью и условиями испытаний [14]. Поэтому выявление закономерностей усталостного поведения автомобильных материалов, полученных по разным технологическим процессам, также является актуальным.…”
Section: Doi: 1017073/0368-0797-2019-9-732-738unclassified
“…Детали автомобиля изготавливаются по разным технологиям [11 -13]. Однако изучение деструкции материалов при усталости осложняется длительностью и условиями испытаний [14]. Поэтому выявление закономерностей усталостного поведения автомобильных материалов, полученных по разным технологическим процессам, также является актуальным.…”
Section: Doi: 1017073/0368-0797-2019-9-732-738unclassified
“…In paper [3], it has been shown that, in order to assess the performance of metal products, in addition to static failure parameters, it is necessary to know the characteristics of fatigue strength, which are significantly dependent on the types and modes of technological treatment. It is noted [4] that it is important not only to develop the technological process of manufacturing of a car element, but also to take into account the totality of all factors that affect service life in the process of subsequent operation [5].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The operating parameters of the structural materials, designated for manufacturing of the automotive metal parts, are formed at all the stages of metal conversion: from the selection of charging materials for metal smelting until obtaining of the finished parts [2,3]. In addition to other factors, the body frame, as well as other elements of the car structure, is also subjected, to fatigue failure in the process of operation, which may lead to a decrease of the working efficiency of the part, and to the irrecoverable consequences and even to loss of lives.…”
Section: Introductionmentioning
confidence: 99%
“…The increased requirements in terms of surface defects -their depth and the presence of a decarburized layer are applied to calibrated rolled stock used for cold die forging [7][8][9]. It is relevant for fasteners used in the components of the motor group of automobiles [10,11].…”
Section: Introductionmentioning
confidence: 99%